2020
DOI: 10.1093/narcan/zcaa010
|View full text |Cite
|
Sign up to set email alerts
|

Proteome dynamics analysis identifies functional roles of SDE2 and hypoxia in DNA damage response in prostate cancer cells

Abstract: Mechanistic understanding of hypoxia-responsive signaling pathways provides important insights into oxygen- and metabolism-dependent cellular phenotypes in diseases. Using SILAC-based quantitative proteomics, we provided a quantitative map identifying over 6300 protein groups in response to hypoxia in prostate cancer cells and identified both canonical and novel cellular networks dynamically regulated under hypoxia. Particularly, we identified SDE2, a DNA stress response modulator, that was significantly downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Nearly 20 years ago, Koshiji et al demonstrated that HIF-1α-rather than other hypoxia-associated genes-that induces the cell cycle arrest [75], which was further confirmed in several genomic and proteomic [31,74,76,77] studies. Cessation of the cell cycle in lymphoma cells was also confirmed in the present work.…”
Section: Discussionmentioning
confidence: 88%
“…Nearly 20 years ago, Koshiji et al demonstrated that HIF-1α-rather than other hypoxia-associated genes-that induces the cell cycle arrest [75], which was further confirmed in several genomic and proteomic [31,74,76,77] studies. Cessation of the cell cycle in lymphoma cells was also confirmed in the present work.…”
Section: Discussionmentioning
confidence: 88%
“…Also, they could function beyond pre-mRNA splicing. Sde2, for example, is reported to regulate the replication stress response ( 21 , 31 , 66 , 67 ) and ribosome biogenesis in humans ( 20 ) and anthocyanin biosynthesis in Arabidopsis ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated the role of these SFs in the development, progression, and prognosis of multiple tumors. [45][46][47][48][49] For example, EIF3A plays a pivotal role in the phenotype and prognosis of bladder cancer by affecting the transcriptome. 49 However, the roles of several other SFs in bladder cancer have not been discussed in previous studies.…”
Section: Discussionmentioning
confidence: 99%